(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2022)
Objective. Evaluate the effect of Telesimulation on academic performance and student satisfaction during the online completion of a clinical subject due to the period of confinement by Covid-19. Methodology. Comparative longitudinal pre-experimental study. The sample was 59 undergraduate students of the Kinesiology degree at the Autonomous University of Chile who took the Clinical Practice II subject online during the autumn period of the year 2021. The intragroup comparisons of the variables academic performance and student satisfaction were determined by t-test for related samples. In all cases a p < 0.05 was adopted. Results. The self-perception of academic performance and satisfaction score increased significantly after the implementation of Telesimulation with standardized patients (p < 0.05). Conclusions. The implementation of Telesimulation with standardized patients significantly improved academic performance and student satisfaction during the COVID-19 confinement. Clinical implication. This teaching strategy could be an integral part of the study plan, supporting the achievement of student learning regardless of the local health status.